Gr-1 blockade remodels the immunosuppressive microenvironment induced by incomplete microwave ablation of hepatocellular carcinoma - Tian Huang; Hensong Cao; Shipeng Dai; Yonghua Zhu; Hanyuan Liu; Shuxian Zhu; Zhengqing Lu; Chuan Liu; Chengyu Lv; Zhouxiao Li; Jinhua Song; Han Zhuo (Cancer Cell International)
Abstract Background Ablation is one of the main methods for local treatment of hepatocellular carcinoma (HCC). Different from radiofrequency ablation (RFA), microwave ablation (MWA) is not limited by tissue conductivity, and can use multiple electrodes at the same time to improve ablation efficiency. In addition, MWA can form a larger ablation area, which makes it possible to completely ablate large HCC. However, MWA may be incomplete due to factors such as larger tumors or tumors in high-risk areas. The mechanism by which the cellular and tumor immune microenvironment (TIME) is involved in the in vitro effects of incomplete microwave ablation (iMWA) needs to be further elucidated. Methods H22 tumor-bearing C57BL/6 mice were treated with iMWA with several combinations of ablation power and time duration. The effects of iMWA on the genes of HCC cancer cells and the TIME were investigated by RNA sequencing, mass cytometry, immunohistochemistry, and immunofluorescence. The effect of iMWA in combination with anti-Gr-1 on HCC tumor growth was also evaluated. Results Thermal stress generated by iMWA induced coagulative necrosis and apoptosis in the region of the ablation center of HCC. RNA sequencing analysis showed that iMWA can boost chemokine CXCL5, which was further confirmed by quantitative real time polymerase chain reaction (qRT-PCR). Mass cytometry results showed that relative to Ctrl group, iMWA-treated led to decreased CD4+ T, CD8+ T, Natural killer (NK), macrophages including both M1 and M2 types but increased monocytes and bone marrow-derived suppressor cells (MDSC). Therefore, inhibiting MDSC is the main target in the later stage of iMWA. In vivo results showed that the tumor volume and weight of iMWA+ anti-Gr-1 group were significantly reduced compared with iMWA+ anti-IgG group. In addition, the merged expressions of CD11b and Gr-1 proteins were found reduced in the iMWA+ anti-Gr-1 group compared with the iMWA+ anti-IgG group by immunofluorescence staining. Immunohistochemistry suggested that CD8 was enriched in the iMWA+ anti-Gr-1 group but not in the iMWA+ anti-IgG group. Conclusion Our data suggests that iMWA and Gr-1 blocking combined therapy can further inhibit HCC growth and significantly improve the CD8+ T cells in the mouse subcutaneous tumor model, which brings good news to HCC patients.